Evolution of 3G Networks The Concept, Architecture and Realization of Mobile Networks Beyond UMTS - Punz, Gottfried; SpringerLink (Online service) (Vienna : Springer Vienna, 2010)
This work covers the status of evolved 3G mobile network technology, as represented by 3GPP$1 (Bs SAE/LTE system, from the "inside" of standardization. It presents architectures, underlying concepts and details of procedures on several levels to promote readers$1 (Bunderstanding of the resulting design and specifications. Remarks on history, detours, and alternatives that were not pursued provide additional insights for non-experts. The author draws on his own notes and observations from standardization meetings, online discussions and company internal analyses, as well as comments and briefings from colleagues around the world, ensuring that readers receive a balanced view and deeper understanding. Gottfried Punz is senior researcher at the network research division of NEC Laboratories Europe and has been active in 3GPP standardization since 2005. He has contributed to the architectural and protocol design of the evolved 3GPP system, with particular focus on CS fallback, home cells and integration with non-3GPP accesses.s
Mobile Networks Evolution -- Architecture of the Evolved 3GPP System -- Main Concepts -- Functions and Procedures of the Evolved 3GPP System -- Protocol Environment.
Keywords: Engineering; Computer science; Telecommunication; Engineering; Communications Engineering, Networks; Models and Principles